Preoperative assessment of the aortic arch in children younger than 1 year with congenital heart disease: utility of low-dose high-pitch dual-source computed tomography. A single-centre, retrospective analysis of 62 cases - Glöckler, Martin; Halbfass, Julia; Koch, Andreas; Dittrich, Sven; Achenbach, Stephan; Rueffer, Andre; Ihlenburg, Katharina Susanne; Cesnjevar, Robert; May, Matthias; Uder, Michael; Rompel, Oliver (European Journal of Cardio-Thoracic Surgery, 2014)
To evaluate the feasibility, image quality and impact of 3D imaging in low-dose high-pitch dual-source computed tomography (DSCT) to assess arbitrary anatomical malformations of the aortic arch in children <1 year of age with congenital heart disease (CHD).Between January 2010 and May 2013, DSCT was performed to assess the aortic arch anatomy in a total of 62 consecutive patients with CHD (aged 0-348 days). DSCT was used whenever conventional echocardiography was not sufficient to display the complex anatomy entirely. Image data acquisition was realized within a single cardiac cycle using prospective ECG triggering. 3D reconstruction for surgical planning was performed. Image quality was assessed retrospectively, using a 4-point scale from '1 = no artefacts' to '4 = uninterpretable'. The accuracy and impact of the 3D reconstructions was compared with intraoperative findings using a 5-point scale (from '1 = essential' to '5 = misleading'). Administered radiation exposure was evaluated.Imaging was successful in all patients, image quality was rated 1.34 on the 4-point scale and the impact of the 3D reconstructions for surgical planning was 2.05 on the 5-point scale. Mean dose-length product was 6.8 ± 2.6 mGy cm, and the effective dose was 0.45 ± 0.13 mSv (0.21-0.74).DSCT is a fast and appropriate imaging modality in the preoperative assessment of the aortic arch for surgical planning in CHD.
EVALuna2:11864

Restoration of endodontically treated teeth with major hard tissue loss - influence of post surface design on pull-out bond strength of fiber-reinforced composite posts - Koch, Andreas; Binus, Stefanie; Holzschuh, Barbara; Petschelt, Anselm; Powers, John M.; Berthold, Christine (Dental Traumatology, 2014)
The aim was to evaluate the influence of post surface design and luting system on bond strength of quartz-fiber-reinforced composite posts (QFRCPs) luted to root canal dentin.Single-rooted bovine teeth (n = 650) were randomly assigned (13 groups, n = 50), sectioned, endodontically treated, filled, and post space (length 8 mm) prepared. Custom-made plain-surfaced fiber posts (PSXRO) and (both RTD) macroretentive Macro-Lock Post Illusion X-RO (MLXRO) were inserted into the post spaces using six luting systems: Ketac Cem (KC), Fuji Plus (FP), RelyX Unicem, Multilink Primer_Multilink, Sealbond Ultima_CoreCem, and LuxaBond_LuxaCore Z. As control, a titanium post was cemented with KC. After water storage (24 h, 37°C), pull-out test was performed, followed by failure mode assessment. Bond strength was calculated in MPa and analyzed using anova, Dunnett-T3-test, and Student's t-test with Bonferroni correction.Post design and luting system significantly influenced the bond strength [MPa] (P < 0.05). Compared with the control 4.3 (1.5), all test groups exhibited higher bond strengths (P < 0.05), except for group PSXRO/KC 4.2 (1.0). The remaining bond strengths were PSXRO: FP 8.6 (1.5), RelyX Unicem 10.4 (3.4), Multilink Primer_Multilink 12.7 (3.0), SealBond Ultima_CoreCem 12.7 (3.0), LuxaBond_LuxaCore Z 15.7 (2.5), and MLXRO: KC 7.2 (2.2), FP 13.4 (2.5), RelyX Unicem 9.2 (2.9), Multilink Primer_Multilink 12.5 (4.5), SealBond Ultima_CoreCem 13.7 (4.6), LuxaBond_LuxaCore Z 20.6 (2.2). The bond strengths of MLXRO were higher than those of PSXRO when luted with KC, FP, and LuxaBond_LuxaCore Z (P < 0.05).The post surface design and luting system selection influenced the bond strength of conventionally and adhesively luted QFRCPs to bovine root canal dentin.
EVALuna2:24661